Evaluation of corn steep powder as a protein source for feed of Nile tilapia Oreochromis niloticus - Hermawan, Dodi; Suprayudi, Muhammad Agus; Jusadi, Dedi; Alimuddin, Alimuddin; Ekasari, Julie (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
This study was aimed to evaluate the use of corn steep powder (CSP) as a plant protein source in Oreochromis niloticus diet. A commercial feed with 28% protein content and 368 kcal/g energy was used as reference diet, while the test feed consisting of various CSP content, namely 0%, 10%, 20%, and 30% and feed containing soybean meal (SBM) at the level of 20% and 30%. Tilapia were used in the trial with the initial body weight of 6.44 ± 0.29 g, and reared for thirty days in the aquarium at the density of fifteen and fed 3 times daily at a satiation level. All diets were supplied by 0.5% of Cr2O3 as an indicator for digestibility measurement. This study applied the completely randomized design experimental method containing six diet treatments and four replications. The result showed that CSP contains 40.27% protein, 26.10% lactic acid, and minerals. CSP is low in crude fiber and anti-nutritional factors. This study results that increasing the level of CSP significantly decreased feed acidity (P <0.05) compared to the control. The addition of CSP 20% increased feed digestibility including protein, lipid, energy, and dry matter digestibility. CSP 20% treatment increased final body weight, specific growth rate and reduced feed conversion ratio significantly (P<0.05) compare to other treatments. In conclusion, CSP can be used up to 20% to improve the growth performance of tilapia. Keyword: corn steep powder, feed digestibility, growth performance, tilapia ABSTRAK Penelitian ini bertujuan mengevaluasi penggunaan corn steep powder (CSP) sebagai sumber protein nabati pada pakan ikan nila Oreochromis niloticus. Pakan komersial dengan kadar protein 28% dan energi 368 kkal/g digunakan sebagai pakan acuan, sementara pakan uji terdiri atas pakan dengan kandungan CSP sebanyak 0% (CSP0), 10% (CSP10), 20% (CSP20) dan 30% (CSP30) serta pakan dengan kandungan tepung bungkil kedelai (SBM) pada level 20% (SBM20) dan 30% (SBM30) sebagai pembanding. Penambahan Cr2O3 0,5 % diberikan sebagai indikator untuk mengukur kecernaan. Ikan nila dengan bobot tubuh rata-rata 6.44 ± 0.29 dipelihara dalam akuarium (95×45×45 cm3) yang diisi air 100 L dengan kepadatan 15 ekor per akuarium dan diberi pakan tiga kali sehari secara at satiation selama 30 hari masa pemeliharaan. Penelitian ini menggunakan desain rancangan acak lengkap dengan enam perlakuan dan empat ulangan. Hasil penelitian menunjukkan bahwa CSP mengandung protein sebesar 40,27%, asam laktat 26,10%, beberapa mineral dan indeks asam amino esensial 0,90. CSP juga rendah serat kasar dan zat antinutrisi. Peningkatan dosis CSP menurunkan pH pakan secara signifikan (P<0.05) dibandingkan dengan kontrol. Penambahan CSP sampai level 20% meningkatkan nilai kecernaan total, kecernaan bahan, kecernaan protein, kecernaan lemak dan kecernaan energi. Di samping itu, perlakuan CSP 20% meningkatkan bobot akhir, laju pertumbuhan harian dan rasio konversi pakan yang signifikan (P<0,05) dibandingkan perlakuan lainnya. Hasil penelitian ini menunjukkan bahwa pemberian CSP 20% dapat meningkatkan kinerja pertumbuhan ikan nila. Kata kunci: corn steep powder, kecernaan pakan, pertumbuhan, ikan nila